Three-dimensional geometric morphometric analysis of the first metacarpal distal articular surface in humans, great apes and fossil hominins. Issue 132 (July 2019) - Galletta, Lorenzo; Stephens, Nicholas B.; Bardo, Ameline; Kivell, Tracy L.; Marchi, Damiano
Abstract: Understanding the manual abilities of fossil hominins has been a focus of palaeoanthropological research for decades. Of interest are the morphological characteristics of the thumb due to its fundamental role in manipulation, particularly that of the trapeziometacarpal joint. Considerably less attention has been given to the thumb metacarpophalangeal (MCP) joint, which plays a role in stabilizing the thumb during forceful grasps and precision pinching. In this study we use a three-dimensional geometric morphometric approach to quantify the shape of the first metacarpal head in extant hominids ( Homo, Pan, Gorilla and Pongo ) and six fossil hominin species ( Homo neanderthalensis Tabun C1 and La Chappelle-aux-Saints, Homo naledi U.W. 101-1282, Australopithecus sediba MH2, Paranthropus robustus /early Homo SK84, Australopithecus africanus StW 418, Australopithecus afarensis A.L. 333w-39), with the aims of identifying shapes that may be correlated with human-like forceful opposition and determining if similar morphologies are present in fossil hominins. Results show that humans differ from extant great apes by having a distally flatter articular surface, larger epicondyle surface area, and a larger radial palmar condyle. We suggest that this suite of features is correlated with a lower range of motion at the MCP joint, which would enhance the thumbs ability to resist the elevated loads associated with the forceful precision grips typical of humans. Great ape genera are each differentiated by distinctive morphological features, each of which is consistently correlated with the predicted biomechanical demands of their particular locomotor and/or manipulatory habits. Neanderthals and U.W. 101-1282 fall within the modern human range of variation, StW 418, SK 84 and U.W. 88-119 fall in between humans and great apes, and A.L. 333w-39 falls within Pan variation. These results agree with those of traditional linear analyses while providing a more comprehensive quantitative basis from which to interpret the hand functional morphology of extinct hominins.